Da arquitetura à não-arquitetura : Gordon Matta-Clark e Rachel Whiteread - Gonçalves, Simone Neiva Loures (2019)
The research is based on the hypothesis that in the recent encounter between art and architecture, termed "complex" by Hal Foster, a field of more positive relations arises than those pointed out by Rosalind Krauss in 1979. The goal of the research is to